The Effects of Corporate Governance, Managerial Ownership and Bonus Plan on Earnings Management: A Case of ASEAN-3 Companies - Silalahi, Alexandermayer H; Warokka, Ari (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2023)
This study is to examine and analyze the effects of corporate governance, managerial ownership, and bonus plan on earnings management of manufacturing and financial companies, which are listed on the Indonesia Stock Exchange, Malaysia Stock Exchange, and the Philippines Stock Exchange. It analyzed the balance sheet data, income, and capital statements presented in the 2008-2012 periods and applied the multiple linear regression analysis and one-way ANOVA to test the proposed hypotheses. The findings showed that corporate governance, managerial ownership, and bonus plan simultaneously did not affect earnings management. There was no significant difference in the proportion of independent board of commissioners, the size of the board of directors, proportion of independent audit committee, managerial ownership, bonus plan, and earnings management between Indonesia, Malaysia, and the Philippines stock exchanges. It implies that the ASEAN-3 companies consider corporate governance unimportant in managing their earnings. It also gives new insights into a rare phenomenon of agency theory findings in semi-strong market efficiency post-global financial crisis 2008.